Modern Slavery: A Global Issue of Exploitation and Injustice - Budiani, Revalio; Rosnawati, Emy; Hasan, Rizqi (Proceedings of The ICECRS, 2023)
This study investigates the evolution of research concerning modern slavery, elucidating its diverse manifestations encompassing human trafficking, debt bondage, forced marriages, and exploitation across industries. The analysis underscores a deficiency in comprehensive synthesis and actionable insights within existing literature. Focused on delineating actionable pathways, this research endeavors to rectify this gap by offering specific recommendations to combat modern slavery effectively. By identifying patterns and lacunae in existing research, this study emphasizes the urgent need for comprehensive interventions to safeguard the rights of the vulnerable and mitigate this pervasive global issue. Highlights: Diverse Manifestations: Modern slavery encompasses varied forms like human trafficking, forced marriages, and industry exploitation. Lack of Synthesis: Existing research lacks comprehensive analysis and actionable recommendations. Urgent Interventions: Emphasizes the critical need for immediate, targeted actions to protect vulnerable groups and combat modern slavery globally. Keywords: Modern Slavery, Exploitation, Global Issue, Intervention, Vulnerable Populations